Pengaruh Substitusi Tepung Talas Kimpul (Xanthosoma sagittifolium) Terhadap Fisikokimia dan Analisis Sensori Brownies Kukus sebagai Alternatif Makanan Selingan Penderita Diabetes Mellitus - Nany Suryani; Putri Nur Azizah; Norhasanah Norhasanah; Ermina Syainah; Rijanti Abdurrachim; Desya Medinasari Fathullah (HB PRESS, 2025)
Cocoyam (Xanthosoma sagittifolium) is a tuber that can provide complex carbohydrates. This study aimed to look at the physicochemical (carbohydrate, protein, fat, crude fiber, ash content, and water content) and sensory analysis of cocoyam steamed brownies as an alternative snack for people with diabetes. This study used an completely randomized design (CRD) with four treatments and three replications using wheat flour and cocoyam flour formulations P0 (100%:0%), P1 (60%:40%), P2 (40%:60%), and P3 (0%:100%). Sensory characteristics were determined using 35 consumer panellists and physicochemical values were determined using proximate. The results of this study show that the highest water content was 2,65%, ash content 23,97 grams in treatment P3, and the highest protein content was 19,64 grams, fat content 17,89 grams, and carbohydrate 19,64 grams in treatment P1. The results of statistical analysis showed that cocoyam flour substitution effect on carbohydrate content (p<0.001), ash content (p=0.008), and water content (p<0.001), but no effect on protein content (p=0.791), fat content (p=0,288), or crude fiber content (p=0,366). The results of sensory analysis showed that P1 was the best treatment with panelists preference level values for color 3,17; aroma 3,0; taste 3,43; texture 2,60 and the results of statistical analysis showed that there was an effect of cocoyam flour substitution on sensory characteristics of steamed brownies, such as colour (p<0.001), aroma (p=0.012), texture (p<0.001), and taste (p<0.001). Cocoyam steamed brownies have a low carbohydrate content of 19.64 g and a high crude fiber content of 21.41 g, the first treatment, brownies (P1), can be used as an alternative snack for people with diabetes.